IONIC LIQUID BASED GEL ELECROLYTES FOR POTENTIAL APPLICATION IN SODIUM ION BATTERY - Noorhaslin Che Su (Tesis, 2020)
Electrolytes as the heart of batteries are the main focus in the study. Iconic liquid based electrolytes have been investigated for sodium batteries to improve safety and performance of the electrolytes as they can be operated in variety of electrochemical devices where they provide wide electrochemical window (>5V) and high thermal stability (up to 300 celcius).